Subjective Well-Being, Politics and Political Economy - Bruno S. Frey (Swiss Journal of Economics and Statistics, 2011)
Happiness research has significantly extended our knowledge about the factors determining individual well-being. Several prominent scholars concluded that governments should engage in maximizing happiness. This approach is based on a technocratic notion that politicians are omniscient benevolent dictators.In contrast, the constitutional approach considers individuals as citizens who, behind the veil of ignorance, choose political rules producing the best possible outcome. Citizens are aware of the Manipulation Principle stating that government tends to distort official happiness indicators in its favour. Citizens therefore demand extensive democratic participation rights allowing them to pursue the kind of happiness they desire.
Keywords: A10; D70; H11; I31; 330; Happiness; well-being; economic policy; manipulation; political economy